SYNDICATE LEARNING: AN ALTERNATIVE APPROACH FOR TEACHING EXTENSIVE READING - Novita, Dian (Journal of Languages and Language Teaching, 2018)
Extensive Reading subject has important benefits for EFL learners. The main purpose of the subject is to raise the positive reading habit for the students. However, for most students, Extensive Reading is not an easy subject to complete. This paper describes the implementation of syndicate learning approach in Extensive Reading subject at English Study Program, Universitas Muhammadiyah Sidoarjo. The studentsâ perceptions of the approach were collected through survey research with opinionative with Likert scales as the instrument. In addition, there were 16 participants engaged in the study. The results showed that majority of the students gave positive views of syndicate learning approach for both as the individual participant and the member of group. The study is expected to contribute a solution for problems may rise in Extensive Reading subject.